Double Portraiture in Art: The Couple Connection - Dorot, Ruth (Journal of Education Culture and Society, 2021)
Aim. The aim of this article is to examine and trace a selection of double portraits all adhering to social codes and norms, from the Renaissance to the present day depicting married couples who were well known in their day and highlighting that artistic fashion especially in northern Europe. Double portraits of a man and a woman are psychologically complex, since they usually provide a visual document of an emotional relationship. The artists’ styles of presentation analyse the characters and relationships of the couples as well as their social status. Methods. The method applied in this paper was that of a qualitative collective case-study based on specific paintings, the comparing and contrasting of which leads to general conclusions. Ten double portraits were selected. They portray well known figures and were painted by a variety of artists. In the second stage, the chosen works were sorted and catalogued chronologically to reflect diversity in terms of people, professions or status. Next, they were analysed on the basis of the language of plastic art: line, colour, light and shadow, composition and overall unifying organization. Results and Conclusions. Since art reflects reality, I demonstrated the development of the field of double portraits across time and how it clearly reflects social change in the role and perception of the wife. Parallel to the development and change in art from the 15th century to the present day, the topic of the double portrait has also changed; each era had its prevailing conventions in terms of fashion, customs, a woman’s status, the development of technology and industry, freedom, liberation, and ‘artistic license’ that surprised, shocked and changed world orders. All these left their mark on the double portrait, which has come a long way from the height of formality to the hovering Chagall and Bella, or the self-annihilation of Picasso.